KAJIAN PENGARUH CAR, NPL, LDR, BOPO, INFLASI, DAN SUKU BUNGA BI TERHADAP KINERJA KEUANGAN SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Rini Setyo Witiastuti; Khaerudin . (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2014)
The purpose of this study is to examine the influence of CAR, NPL, LDR, BOPO, Inflation, and BI Rate on ROA in banking sector listed in Indonesia Stock Exchange (IDX) within 2008 - 2012. The examination took the population of all banks listed in Indonesia Stock Exchange within the research period. Taken from the sampling, there are 23 banks. It also used the classical assumption test and multiple regression analysis (t test). The result of this research shows that CAR, LDR, and Inflation have positive but not significant effect on ROA; NPL and BOPO have negative and significant effect on ROA; and BI rate has negative but not significant effect on ROA in banking sector listed in Indonesia Stock Exchange (IDX) period 2008-2012. Keywords: Bank Financial Ratios, Inflation, BI Rate, Financial Performance